Regulation of Signal Transduction in Human Cell Research (Current Human Cell Research and Applications, 2018)
This volume focuses on the relationship between the regulation of signal transduction and disease mechanisms, and discusses how the dysregulation of intracellular signals cause diseases, cell death, carcinogenesis, and other disorders. Growth, survival, transformation, and metabolic activities at the cellular level are regulated by various intracellular signal transduction pathways. Sources that stimulate intracellular signals include intracellular stresses and signal regulators/modulators, as well as extracellular growth factors. Recent studies on signal transduction analysis using animal and human cell lines have revealed how the intracellular signals are regulated and why their dysregulation leads to pathological states such as tumorigenesis, metabolic diseases, cell death, and so on. This book highlights several important key molecules and intracellular signaling pathways such as microRNA, the TGF-beta signaling pathway, the Wnt signaling pathway and MET signaling pathway as topical and highly relevant issues in human cell research related to signal transduction. In addition to assessing the pathogenic role of these signaling pathways, it focuses on the molecular design of small molecule regulators/inhibitors of said pathways, one of the most important approaches in this area. This book offers a valuable guide, helping not only research scientists but also clinicians to understand how the dysregulation of intracellular signals leads to diseases.